Building Brand Awareness through Cultural Sensitivity: Factors Influencing Customer Loyalty in Indonesian Restaurants in Taiwan - Syahruddin, Syahruddin; Mujahida, Sitti; Azizurrohman, Muhammad; Dewayani, Eka Kadharpa Utama (UI Scholars Hub, 2024)
Research Aims: With cultural sensitivity acting as a moderating factor, this study investigates the effects of pricing strategy, cleanliness, meal quality, and service quality on customer loyalty and brand recognition of Indonesian restaurants in Taiwan. Design/Methodology/Approach: Four hundred overseas respondents participated in a structured survey; partial least squares (PLS) and structural equation modelling (SEM) were used to analyse the results. Research Findings: The findings indicated that while service quality and cleanliness had no discernible impact, food quality and pricing strategy greatly enhanced consumer loyalty. Cultural sensitivity bolstered the favourable correlation between loyalty and food quality. Theoretical Contribution/Originality: The study adds to the body of knowledge in marketing by emphasising how crucial cultural sensitivity is to building patronage in foreign ethnic eateries. Managerial Implication: The results highlight the importance of food quality and price strategies for Indonesian restaurant owners in Taiwan, together with the integration of cultural components to cultivate brand awareness and loyalty. Additionally, they must enhance both the hygiene of their eateries and their marketing campaigns. Research Limitation & Implications: The results' generalisability may be limited by the study's focus on international clients in Taiwan; therefore, ambiance and menu diversity should be taken into account in future studies. A more thorough understanding of customer satisfaction and loyalty would be possible by diversifying the client base and investigating new markets.